Peningkatan Kompetensi Keguruan Melalui Program Praktik Pengalaman Lapangan di MTsN 7 Aceh Utara - Mulyana, Mulyana; Arija, Marsal; Musdar, Musdar; Rahmat, Aulia (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
In an effort to enhance the teaching competencies of students, the Field Experience Program (PPL) at MTsN 7 Aceh Utara was implemented with the goal of applying educational theory in real-world practice. This study employs an action research approach with a classroom action research design, involving cycles of planning, implementation, observation, and reflection. The research methods include observation, interviews, documentation, and self-reflection by the practitioners. The collected data were analyzed descriptively to identify patterns and necessary improvements in the teaching process. The findings indicate that the implementation of PPL successfully improved practitioners' skills in determining and preparing teaching materials, applying effective teaching techniques, and developing well-structured Lesson Plans (RPP). Practitioners also gained direct teaching experience, enhanced classroom management, and better understood student characteristics. Additionally, the use of teaching media was refined, contributing to an increased understanding of the material by students. Although the PPL program yielded positive results, several challenges such as student attitudes and preparedness emerged. Efforts to address these challenges included regular consultations with supervising teachers, creating a conducive learning environment, personal approaches with students, and providing motivation. The recommendations from this study are the reinforcement of classroom management strategies, increased student participation through personal approaches, and the use of more varied teaching media to support a more effective teaching and learning process.